Konsep Infaq Dalam Hukum Islam: Pengertian, Rukun, Etika, Dan Implementasinya - Edi Hermanto; Guslina Siregar; Naila Agnia Ramadhani; Saima Putri Nurfatimah Nst (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study examines the concept of infaq in Islamic law as a spiritual obligation and a social instrument aimed at fostering justice, compassion, and communal welfare. Infaq, derived from the Arabic term anfaqa–yunfiqu–infāqan, refers to the voluntary or obligatory expenditure of wealth for purposes commanded by Allah, encompassing both personal responsibilities such as family support and broader societal needs including poverty alleviation, education, healthcare, and community development. Unlike zakat, infaq is not bound by the requirements of nisab and haul, allowing all Muslims regardless of economic capacity to participate in acts of giving. The Qur’an, particularly in Surah Al-Baqarah 2:261–262, emphasizes that the value of infaq lies not merely in the amount given but in the sincerity, humility, and proper ethics of the giver. Classical exegetes such as Ibn Kathir and Al-Maraghi stress that mann (reminding others of one’s gifts) and adza (hurting the recipient) nullify the spiritual merit of infaq, highlighting the moral dimension of giving.The study outlines the pillars and conditions required for the validity of infaq, including the giver, the recipient, the property being given, and the expression of consent. It further categorizes infaq into permissible, obligatory, prohibited, and recommended forms. Ethical principles include secrecy, empathy, consistency, and giving according to one’s means. The research also discusses the spiritual, social, and economic benefits of infaq, such as purifying the soul, eliminating miserliness, enhancing social solidarity, and promoting economic balance. In the contemporary era, infaq is implemented through humanitarian assistance, education programs, health services, disaster relief, and community empowerment initiatives.